Labor-Use Efficiency in Saudi Manufacturing Sectors - Saggay, Ali; Raies, Asma (Journal of Reviews on Global Economics, 2018)
This paper seeks to examine the process of adjustment in labor and to measure labor-use efficiency in Saudi manufacturing sectors. The theoretical framework is based on a dynamic flexible adjustment model applied to a panel of seven Saudi industries observed from 2007 to 2015. It investigates the process of adjustment in labor Saudization level toward a desired level. The adjustment process is both industrial and time-specific, and is expressed in terms of factors affecting the speed of adjustment. The empirical results show that, in the long run, labor Saudization responds greatly to gross domestic product, followed by unit Saudi wage and least by non-Saudi labor. In addition, labor over-use in Saudi manufacturing sectors is reduced after application of Nitaqat program.